Analisis Kesesuaian Penerapan Sistem Proteksi Kebakaran, Sarana Penyelamatan Jiwa, dan Pengorganisasian Pada Gedung Y PT X Tahun 2021 - Raza Adhanzio Khairasyid, (2021)
Electrical short circuits caused 62 percent of fire accidents in Depok City in the last five years, according to data from the Depok City Fire Department (2021). The Y building was experienced a fire in 2017 due to an electrical short circuit. The Y Building, which has 20 floors, is required to implement fire protection management, such as the application of fire protection systems, life-saving facilities and organization. These things aim to minimize or even eliminate losses that may arise if fires occur again, according to the Minister of Public Works Regulation No. 20 of 2009. The goal of this study was to determine if the Y Building's application of fire prevention systems, life saving facilities and organization complied with existing regulatory criteria. A descriptive study design and a qualitative technique were used in this study. The results of this study indicate that the application of a passive protection system at the Y Building is included in the Enough category (C), the application of an active protection system is included in the Enough category (C) , the application of life saving facilities are included in the Enough category (C) and the implementation of organizations is included in the Less category (K). It can be seen from this study that the application of fire protection systems, life saving facilities, and organizations in Building Y has not been included in Good category or in accordance with the existing standards